PENGARUH KEPEMIMPINAN DAN KARAKTERISTIK PEKERJAAN TERHADAP KINERJA DENGAN MODERASI BUDAYA ORGANISASI (Studi pada Perawat Puskesmas di Kabupaten Temanggung) - 11.5202.0105, Sri Hartati (Jurnal Mahasiswa Pasca Sarjana, 2013)
This research aims to descrip and analyze the effect of leadership and job characteristics on nurses performance and the effect of leadership and job characteristics on nurses performance organizational culture with moderation. The research located at 24 community health center in kabupaten temanggung. Research Sample amount to 131 respondent by using sensus sampling method.Models to be developed during the research are four hypothecal models, which go for the multiple regression analyze and moderation regression analyze method of SPSS analitycal device.The result of research showed that variable of leadership and job characteristics have a positive and significant influence on nurses performance, job characteristic have the most dominant influence on nurses performance. Organisational culture cannot moderate the influence of leadership and job characteristics on nurses performance. Keywords : leadership, job characteristic, organizational culture and performance.